The Effect of Product Quality and Promotional Activities on Purchasing Decisions Mediated by The Price of Bear Brand Milk Drink Products During The Covid-19 Pandemic - Surya Bintarti -; Ergo Nurpatria Kurniawan; Fendy Manunggal W; M. Alwi (Enrichment : Journal of Management, 2022)
The purpose of this study is to examine and determine the influence of promotion and product quality on purchasing decisions with price mediation on Bear Brand products. In this survey, there were 75 consumer respondents who were sampled. The data analysis test in this study was carried out using the Smart PLS program, the analysis technique in this scientific paper uses the SmartPLS 3.3.3 program. The results showed that: (1) price has a positive and significant effect on purchasing decisions; (2) product quality has a positive and significant effect on price; (3) promotion also has a positive and significant influence on the price.